Analysis of Nursing Care with the Application of Brain Gym to Reduce Blood Pressure in Elderly with Hypertension - Nassya Abdi; Siska Sari; Mike Wulandari; Yumiati (CV Media Inti Teknologi, 2026)
Background of study: Hypertension is a circulatory system disorder that causes blood circulation above normal 120/80 mmHg. Health problems in the elderly include physical problems, cognitive problems, emotional problems, spiritual problems, and psychosocial problems. Physical problems include hypertension. Non-pharmacological blood pressure management can be done by applying brain gym therapy.Aims and scope of paper: This scientific paper aims to analyze nursing care for Mr. J and Mr. B and evaluate the application of brain gym therapy in reducing blood pressure in elderly people with hypertension at the UPT PSTW Husnul Khotimah, Riau Province Social Service, correctly, and in accordance with professional nursing standards.Methods: This application uses a one-group pretest-posttest design using 2 subjects. This research instrument uses an observation sheet. The intervention was administered from December 1-3, 2025. This intervention was carried out for 10 minutes for 3 consecutive days in the morning.Result: The results of blood pressure reduction for 3 days in Mr. J with an average systolic value of 10 mmHg and diastolic 13 mmHg. While the reduction in blood pressure for 3 days in Mr. B with an average systolic value of 11 mmHg and diastolic -1 mmHg.Conclusion: The conculusion of brain gym therapy have been proven to reduce blood pressure.